Correlates of Organizational Commitment Among Community Correctional Officers in China - Jiang, Shanhe (The prison journal, 2018)
There has been limited research on the correlates of organizational commitment among community correctional staff, regardless of the nation. Using data from 225 community correction officers from Hubei, China, this study examined community correctional staff commitment to their agencies and its predictors. The study found the majority of the respondents had commitment to their organizations. Organizational structure variables were more powerful than job characteristics in explaining the variance of the organizational commitment. All relationships between organizational structure variables, job characteristics, and organizational commitment were mediated by job satisfaction.